2023
DOI: 10.1097/lvt.0000000000000185
|View full text |Cite
|
Sign up to set email alerts
|

Redo hepatic artery reconstruction for thrombosis without retransplantation in 1355 adult living donor liver transplantations

Abstract: Hepatic artery thrombosis (HAT) after liver transplantation is associated with a marked increase in morbidity, leading to graft and patient loss. We evaluated the outcomes of adult living donor liver transplantation patients with HAT under an aggressive surgical intervention. A total of 1355 recipients underwent adult living donor liver transplantation at the Seoul National University Hospital. Surgical redo reconstruction for HAT was performed in all cases except in those with graft hepatic artery injury and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…
To the editor, We would like to express our gratitude to Guo et al for their interest and comments on our publication, "Redo hepatic artery reconstruction for thrombosis without retransplantation in 1355 adult living donor liver transplantations." [1] Their insightful observations and constructive opinions are valuable in furthering the discussion on this topic.In the procedure of surgical revascularization after hepatic artery thrombosis (HAT), it is preferred to use the initially anastomosed hepatic artery (HA) for reconstruction if its quality and length are acceptable. [2] If the length after removal of the damaged part is short or the quality of the existing HA is poor, using an alternative HA is the next option.
…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…
To the editor, We would like to express our gratitude to Guo et al for their interest and comments on our publication, "Redo hepatic artery reconstruction for thrombosis without retransplantation in 1355 adult living donor liver transplantations." [1] Their insightful observations and constructive opinions are valuable in furthering the discussion on this topic.In the procedure of surgical revascularization after hepatic artery thrombosis (HAT), it is preferred to use the initially anastomosed hepatic artery (HA) for reconstruction if its quality and length are acceptable. [2] If the length after removal of the damaged part is short or the quality of the existing HA is poor, using an alternative HA is the next option.
…”
mentioning
confidence: 98%
“…To the editor, We would like to express our gratitude to Guo et al for their interest and comments on our publication, "Redo hepatic artery reconstruction for thrombosis without retransplantation in 1355 adult living donor liver transplantations." [1] Their insightful observations and constructive opinions are valuable in furthering the discussion on this topic.…”
mentioning
confidence: 98%
“…Retransplantation is an early option, but is limited by donor shortages. The recent study by Hong et al, 2 published in Liver Transplantation , evaluated the outcomes of adult living donor liver transplantation patients with HAT under an aggressive surgical intervention. The study found that successful revascularization saved the graft without retransplantation in 96.0% of the cases.…”
mentioning
confidence: 99%